2023
DOI: 10.3390/jpm13121676
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Platelet-Rich Plasma (PRP) in Infertility—Infusion versus Injectable PRP

Ioana Alexandra Zaha,
Anca Huniadi,
Florin Bodog
et al.

Abstract: (1) Background: During IVF (in vitro fertilization) procedures, endometrial thickness has a significant role in the success of pregnancy outcomes for embryo transfers. Endometrial thickness, a crucial component of endometrial receptivity, is a contentious issue. The regenerative properties of PRP have been shown in recent research to have positive effects on the endometrium. PRP increases the pregnancy rate in IVF patients with thin endometrium and recurrent implantation failure. In order to demonstrate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…PRP is a concentrated solution of platelets that is rich in growth factors, showing the ability to facilitate angiogenesis, neuroprotection, neural regeneration, regulation of inflammation with broad therapeutic applications [17,[32][33][34][35][36][37][38][39][40][41][42]. Comparative studies have shown the clinical advantages of PRP injection for patients with incomplete RC tears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRP is a concentrated solution of platelets that is rich in growth factors, showing the ability to facilitate angiogenesis, neuroprotection, neural regeneration, regulation of inflammation with broad therapeutic applications [17,[32][33][34][35][36][37][38][39][40][41][42]. Comparative studies have shown the clinical advantages of PRP injection for patients with incomplete RC tears.…”
Section: Discussionmentioning
confidence: 99%
“…The Constant-Murley score (CMS) is a standardized scale for evaluating shoulder function, with a maximum score of 100 denoting optimal shoulder function. This scoring system has been employed in numerous studies for evaluating shoulder-related outcomes [4,[16][17][18]. Shoulder ROM was evaluated with the patient seated.…”
Section: Clinical Assessmentsmentioning
confidence: 99%
“…In an in vitro study, active PRP stimulated the migration of human endometrial epithelial cells, stromal fibroblasts, and mesenchymal stem cells, and additionally, activated PRP increased the proliferation of endometrial stromal cells and mesenchymal cells [21]. PRP increased the EM thickness and improved the EM receptivity through the effect of cytokine regeneration [22]. The first report on the intrauterine infusion of autologous PRP for patients with persistent thin EM was published in 2015, demonstrating the efficacy of PRP treatment in increasing EM thickness and improving pregnancy rates after FET [23].…”
Section: Introductionmentioning
confidence: 99%